Enhancing the developmental competence of bovine oocytes and embryos - Alhilfi, H.O. (2018)
Enhancing the developmental competence of oocytes and quality of embryos is central to the success of in vitro embryo production (IVP) both in human and animal laboratories. However, there is currently no optimal protocol for IVP in either a commercial or clinical setting that leads to high yields of developmentally competent embryos and pregnancy outcomes. The current series of studies were performed to establish the effects of nitric oxide donor (Sodium nitroprusside (SNP)) and the proteasome inhibitor (MG132) on nuclear maturation and mitochondrial activity of bovine oocytes. Also, to establish the effects of Transforming Growth Factor B1 (TGFB1) and Colony Stimulating Factor 2 (CSF2) added to embryo culture (IVC) on the development of bovine embryos beyond morulation.